Pemilihan Bangunan Pelindung terhadap Bencana Hidrometri Basah dalam Rekayasa Sumberdaya Air - Mera, Mas; Yuhendra, Rahmad; Wahyudi, Reski; Wilman, Wilman; Putra, Rifky (Jurnal Rekayasa Sipil (JRS-Unand), 2024)
Inaccuracy in selecting the type of water resources structures as protection structures against wet hydrometric disasters means that the effects of the disaster are not reduced significantly. This situation gets worse if the placement of the protection structures is not correct. This research focuses on selecting the type and location of protection structures against wet hydrometric disasters in water resources engineering so that they work optimally. This optimization is carried out by maximizing the function of the structures as protector against hydrometric disasters, and minimizing new disasters that may arise due to the presence of these protection structures. The first stage is to identify the behavior and to predict the characteristics of water at location of the wet hydrometric disaster and its surroundings. This is done by analyzing video and aerial photos in several circumstances. The next stage is to select the appropriate type of protection structures. The final stage is to determine the location and dimensions of the protection structures with the consideration that new disasters that may arise due to the presence of the protection structures must be relatively small. Another consideration for determining the dimensions of a structure is the characteristics of the water. Determination of the location and dimensions of the protection structures are carried out using theoretical simulations. The results of research in the field show that protection structures work optimally and with relatively small dimensions and numbers, and is in accordance with theoretical estimates.